The Implementation of Mindful Self-Compassion in Managing Academic Emotions through Islamic Religious Education and Character Education Learning at Senior High School - Farida, Farida; Wibowo, Mungin Eddy; Purwanto, Edy; Sunawan, Sunawan (EDUKASIA, 2026)
This study aims to investigate the implementation of mindfulness, particularly mindful self-compassion, in managing academic emotions in Islamic Religious Education and Character Education learning at SMA 1 Bae. This study addresses the absence of a holistic approach in assessing students’ spiritual development, particularly in terms of emotional management under academic challenges. Integrating mindfulness into Islamic Religious Education and Character Education learning is viewed as a vital teaching method to improve students’ emotional balance and spiritual well-being. A descriptive qualitative method was employed, involving in-depth interviews with students, Islamic Religious Education and Character Education teachers, and school counselors. Observations and thematic analyses were also conducted to obtain a comprehensive understanding of the participants’ experiences. The findings reveal that mindfulness practices encompassing self-kindness, common humanity, and mindful awareness help students manage academic anxiety, cope with failure, and build hope, empathy, and positive social interactions. The integration of mindfulness into Islamic Religious Education and Character Education learning not only strengthens students’ emotional management but also fosters their character and spiritual development. This study contributes to the development of a comprehensive model of religious education that extends to cognitive assessment by focusing on students' emotional and spiritual well-being in the context of secondary education.